1994
DOI: 10.1073/pnas.91.19.8935
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of the UDP-N-acetyl-D-galactosamine: polypeptide N-acetylgalactosaminyltransferase-mediated O-glycosylation reaction in the submaxillary gland.

Abstract: Addition of N-acetylgalactosamine to threonine and serine is the first step in the synthesis of O-glycosidically linked oligosaccharides. A UDP-N-acetyl-D-galactosamine:polypeptide N-acetylgalactosaminyltrnsferase (EC 2.4.1.41) from porcine submaillary glands was recently purified to electrophoretic homogeneity, and polyclonal antibodies against the purified transferase were raised. Immunoblots of porcine, bovine, and ovine submaxillary gland extracts with the anti-tansferase antibodies gave a single band and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 41 publications
4
75
0
Order By: Relevance
“…4) Mucin-type O-glycosylation of SP85 and other cell surface glycoproteins in Dictyostelium, including contact sites A/gp80 and SP29, is posttranslational based on developmental and pulse-chase studies (18,5), and the morphological equivalent of Golgi stacks are seen in developing prespore cells at a time when O-glycosylation of spore coat proteins is maximal (44). Together these observations strongly support the model that pp ␣-GlcNAc-T2 is a type 2 membrane protein, in contrast to pp ␣-GlcNAc-T1 but like other known Golgi glycosyltransferases (35), and that it resides in a post-rER secretory compartment, probably the Golgi, as seen for the animal pp ␣-GalNAc-Tases (45,9).…”
Section: Figsupporting
confidence: 67%
“…4) Mucin-type O-glycosylation of SP85 and other cell surface glycoproteins in Dictyostelium, including contact sites A/gp80 and SP29, is posttranslational based on developmental and pulse-chase studies (18,5), and the morphological equivalent of Golgi stacks are seen in developing prespore cells at a time when O-glycosylation of spore coat proteins is maximal (44). Together these observations strongly support the model that pp ␣-GlcNAc-T2 is a type 2 membrane protein, in contrast to pp ␣-GlcNAc-T1 but like other known Golgi glycosyltransferases (35), and that it resides in a post-rER secretory compartment, probably the Golgi, as seen for the animal pp ␣-GalNAc-Tases (45,9).…”
Section: Figsupporting
confidence: 67%
“…We have observed that newly synthesized CD8-K and CD8-E19, in contrast to CD8-S and unmodified CD8, require several hours to undergo the initial O-glycosylation events. There is compelling evidence that these events occur in the cis/medial Golgi compartments (Roth et al, 1994;Piller et al, 1989;Verde et al, 1995;Vassard et al, 1995). This finding may thus support the view of efficient retrieval occurring upstream of these compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The polypeptide GalNAc-transferases are distributed throughout the Golgi cisternae, but there is evidence for some differences in distribution among isoforms (33,34). The Oglycan processing step, involving initiation, elongation, branching, and termination of oligosaccharide chains, is believed to occur throughout the Golgi stacks and in the trans-Golgi network (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%